Analisis Materi Sulit Dipahami Dan Miskonsepsi Mahasiswa Program Studi Pendidikan Matematika STKIP Hermon Timika Dalam Mata Kuliah Kalkulus Pada Materi Integral - Rasul, A.; Subhanudin; Hilal, Nurul; Sonda, Ruben (Yayasan Pendidikan Internasional Bengkulu, 2023)
This study aims to analyze and describe what materials are difficult in calculus courses and also materials that are misconceptions. This research was conducted to improve the competence of students in the future. The formulation of the problem in this study is